Perancangan Antarmuka Pengguna Interaktif untuk Aplikasi UTBKing dengan Pengembangan Model - Florentina Yuni Arini; Gerard Sean Dwayne; Aisyah Nathania Araminta; Inoru Nian Alfita; Ahmad Zidhan Ilmana; Nathania Adristina (Universitas Negeri Semarang, 2024)
Higher education is crucial for personal development, yet its accessibility often poses a challenge, especially for economically disadvantaged students. Apps like UTBKing aim to provide easily accessible learning resources, aiding students in preparing for college entrance. The development process involves three main stages: data collection, system development, and system design. The discussion will delve into the detailed flow of the UTBKing app, its UI/UX design, and implemented interactive features. Continuous efforts are required to develop and enhance the quality of learning applications in order to provide optimal benefits for students in facing future academic challenges.